The Evolution of Information Literacy and Technology in the KU Academic Accelerator Program - Stamer-Peterson, Melissa (Issues in Language Instruction, 2018)
The Kansas University Academic Accelerator Program (KUAAP) began in the fall of 2014. During the first term, all but a handful of students were required to take AAPT 001: Introduction to Technology for Academic Purposes. The focus of this one-credit course was to teach students how to function in a university academic setting using and optimizing technology. This was the first class in a two-course sequence where the second class, AAPT 002 (it was never officially named past its abbreviation because it was never offered), would focus on research skills and plagiarism which built on the foundation from the previous term.